An exploration of the causes, manifestations and consequences of tuberculosis stigma in an urban district in Ghana - Dodor, Emmanuel Atsu (2009)
This thesis used a qualititave research approach to explore the causes, manifestations and consequences of tuberculosis (TB) stigma in an urban district in Ghana. It examined reasons why TB is stigmatised and elucidated how TB stigma manifests within the community setting and the healthcare system. It also explored the feelings and experiences of TB patients, to highlight how the fear of stigmatisation may affect case finding and treatment adherence.